1993
DOI: 10.1002/aja.1001970407
|View full text |Cite
|
Sign up to set email alerts
|

Second messenger regulation of occlusion of the spinal neurocoel in the chick embryo

Abstract: We know that, once rostra1 neurulation is completed in the neuroaxis of the chick embryo, the caudal neurocoel becomes occluded and the brain rapidly expands. However, very little is known about the mechanisms maintaining occlusion. Studies had shown that occluded neurocoels reopened in embryos treated with chelators of cations, but the reasons remained unclear and the cations unidentified. To begin defining the role of cations, this study explored the effect of CaZC, calmodulin, and cAMP on maintaining the oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…This relation could be explained if we bear in mind that the osmotic pressure of NTF implies an increase of water inside the brain cavity, leading to an increase in hydrostatic pressure and/or a neuroepithelial wall distension. This explanation is based on the assumption that the embryonic brain is a physiologically sealed system (Schoenwolff and Desmond, 1984;Desmond et al, 1993). These data support the hypothesis that NTF osmolality could be involved in the control of brain expansion.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…This relation could be explained if we bear in mind that the osmotic pressure of NTF implies an increase of water inside the brain cavity, leading to an increase in hydrostatic pressure and/or a neuroepithelial wall distension. This explanation is based on the assumption that the embryonic brain is a physiologically sealed system (Schoenwolff and Desmond, 1984;Desmond et al, 1993). These data support the hypothesis that NTF osmolality could be involved in the control of brain expansion.…”
Section: Discussionsupporting
confidence: 63%
“…The explosive growth of the embryonic brain cavity has been directly related to the expanding force generated by the positive pressure of the intraluminal fluid described by Jelinek and Pexieder (1968). Such pressure requires the previous occlusion of the spinal cord lumen, transforming the brain cavity into a physiologically sealed system (Schoenwolf and Desmond, 1984;Desmond et al, 1993). The particular role, based on physical phenomena, that these morphogenetic mechanisms can play in the developmental pattern of various embryonic anlages was summarized by Newman and Comper (1990).…”
mentioning
confidence: 98%
“…However, it resembles the process of occlusion of the neural tube in the rhombocervical region. Occlusion is regarded as a normal event during early embryogenesis and has been described for human (Desmond, 1982;Mü ller and O'Rahilly, 1986), mouse (Kaufman, 1983;Shum and Copp, 1996), rat (Freeman, 1972), chick Desmond, 1984, 1986;Desmond andSchoenwolf, 1985, 1986;Desmond et al, 1993), and salamander (Lofberg et al, 1980). Occlusion results in a physiological sealing of the neural tube, and it has been proposed that complete occlusion of the neural canal plays an important part in facilitating enlargement of the brain (Coulombre and Coulombre, 1958;Desmond and Jacobson, 1977).…”
Section: Occlusionmentioning
confidence: 99%
“…However, studies carried out in chick embryos indicate that the expansive process starts with the occlusion of the spinal cord lumen and the closure of the anterior neuropore; this transforms the brain vesicle cavity into a physiologically sealed system [Schoenwolf and Desmond, 1984;Desmond et al, 1993], inside which the neural tube fluid (NTF) exerts a positive pressure against the neuroepithelial walls and generates an expansive force, described and quantified by Pexieder [1968, 1970]. Desmond and Jacobson [1977] demonstrated that the experimental decrease in NTF pressure leads to severe dysmorphogenesis and brain collapse, thus revealing the involvement of this fluid's pressure in brain anlage growth in the chick embryo.…”
Section: Introductionmentioning
confidence: 99%